Nonsurgical management of an extensive spontaneous spinal epidural hematoma causing quadriplegia and respiratory distress in a choledocholithiasis patient: A case report. Issue 51 (December 2017) - Raasck, Kyle; Khoury, Jason; Aoude, Ahmed; Abduljabbar, Fahad; Jarzem, Peter
Abstract: Rationale: Spontaneous spinal epidural hematoma (SSEH) manifests from blood accumulating in the epidural space, compressing the spinal cord, and leading to acute neurological deficits. The disease's cloudy etiology and rarity contribute to dangerously suboptimal therapeutic principles. These neural deficits can be permanent, even fatal, if the SSEH is not treated in a timely and appropriate manner. Standard therapy is decompressive laminectomy, though nonsurgical management is a viable course of action for patients who meet a criterion that is continuously being refined. Patient concerns: A 76-year-old woman on warfarin for a past pulmonary embolism presented to the emergency room with jaundice, myalgia, hematuria, neck pain, and an International Normalized Ratio (INR) of 14. Upon admission, she rapidly developed quadriplegia and respiratory distress that necessitated intubation. Diagnoses: T2-weighted magnetic resonance imaging (MRI) revealed an epidural space-occupying hyperintensity from C2 to S5 consistent with a spinal epidural hematoma. An incidental finding of dilated intrahepatic and common bile ducts prompted an endoscopic retrograde cholangiopancreatography, which demonstrated choledocholithiasis. Interventions: The patient's INR was normalized with Vitamin K and Beriplex. Upon transfer to the surgical spine team for assessment of a possible intervention, the patient began to demonstrate recovery of neural functions. The ensuing sustained motor improvement motivated the team's preference for close neurologic monitoring and continued medical therapy over surgery. Thirteen hours after the onset of her symptoms, the patient was extubated. A sphincterotomy was later performed, removing 81 common bile duct stones. Outcomes: MRI demonstrated complete resorption of the SSEH and the patient maintained full neurological function at final follow-up. Lessons: Nonsurgical management of SSEH should be considered in the context of early and sustained recovery. Severe initial neural deficit does not necessitate surgical decompression. Choledocholithiasis and subsequent Vitamin K deficiency, particularly when coupled with anticoagulant use, can increase INR and is a novel proposed risk factor for SSEH. Furthermore, coagulopathies should be medically corrected before surgical intervention within a given timeframe, as spontaneous recovery may manifest. This should be favored over surgery in patients demonstrating early and sustained recovery, as nonsurgical management is 25% more effective in achieving full recovery.